IMPLEMENTASI FINANCIAL TEKNOLOGI QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) DALAM EFISIENSI PEMBAYARAN PADA UMKM DI BANDAR LAMPUNG - Sabila, Tamam; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
MSME stands for Micro, Small, and Medium Enterprises. MSMEs have an important role in improving the national economy. Based on data from the Ministry of Cooperatives and SMEs, the number of MSMEs currently reaches 64.2 million with a contribution to GDP of 61.07% or 8,573.89 trillion rupiah. However, the high number of MSMEs in Indonesia is also inseparable from the challenges and limitations that exist. These challenges and limitations make it difficult for MSMEs to develop and compete with other businesses. The minimal use of technology in making transactions more efficient in MSMEs is still one of the problems. This study aims to determine how the implementation of QRIS (Quick Response Code Indonesian Standard) financial technology in payment efficiency in MSMEs in Bandar Lampung. From the results of the research conducted by the researcher, the implementation of QRIS (Quick Response Code Indonesian Standard) financial technology in payment efficiency in MSMEs in Bandar Lampung In Bandar Lampung City, MSME entrepreneurs have begun to innovate to further increase efficiency and ease of accessing financial services. Currently, MSME entrepreneurs choose QRIS fintech to facilitate financial access services and make transactions more efficient in doing business. Because of the many benefits of using QRIS in MSMEs that can be felt by users and merchants.